Access to FeII Bis(σ‐B−H) Aminoborane Complexes through Protonation of a Borohydride Complex and Dehydrogenation of Amine‐Boranes. Issue 39 (19th August 2019) - Gorgas, Nikolaus; Stöger, Berthold; Veiros, Luis F.; Kirchner, Karl
Abstract: Herein, we report on the first synthesis and structural characterization of the iron based aminoborane complexes [Fe(PNP)(H)(η 2 :η 2 ‐H2 B=NR2 )] + (R=H, Me). These species are formed upon protonation of the borohydride complex [Fe(PNP)(H)(η 2 ‐BH4 )] by ammonium salts [NH2 R2 ] + (R=H, Me). For R=Me, the reaction proceeds via the cationic dinuclear intermediate [{Fe(PNP)(H)}2 (μ 2, η 2 :η 2 ‐BH4 )] + . A mechanism for the reaction is proposed based on DFT calculations that also indicate the final aminoborane complex as the thermodynamic product. All complexes were characterized by NMR spectroscopy, HRMS, and X‐ray crystallography. Abstract : The first synthesis and structural characterization of Fe II based aminoborane complexes of the type [Fe(PNP)(H)(η 2 :η 2 ‐H2 B=NR2 )] + (R=H, Me) is reported. These species are formed upon protonation of the borohydride complex [Fe(PNP)(H)(η 2 ‐BH4 )] by ammonium salts NH2 R2 + (R=H, Me).